H.C.F. of Polynomials by Factorization

Learn how to solve H.C.F. of polynomials by factorization splitting the middle term.

Solved examples on highest common factor of polynomials by factorization:

1. Find out the H.C.F. of x2 - 3x - 18 and x2 + 5x + 6 by factorization.

Solution:

First expression = x2 - 3x - 18

                      = x2 - 6x + 3x - 18, by splitting the middle term - 3x = - 6x + 3x

                      = x(x - 6) + 3(x - 6)

                      = (x - 6) (x + 3)

Second expression = x2 + 5x + 6

                          = x2 + 3x + 2x + 6, by splitting the middle term 5x = 3x + 2x

                          = x(x + 3) + 2(x + 3)

                          = (x + 3) (x + 2)

Therefore, in the two polynomials (x + 3) is the only common factors, so, the required H.C.F. = (x + 3).


2. Find out the H.C.F. of (2a2 - 8b2), (4a2 + 4ab - 24b2) and (2a2 - 12ab + 16b2) by factorization.

Solution:

First expression = (2a2 - 8b2)

                      = 2(a2 - 4b2), by taking common 2

                      = 2[(a)2 - (2b)2], using the identity of a2 – b2

                      = 2(a + 2b) (a - 2b), we know a2 – b2 = (a + b) (a – b)

                      = 2 × (a + 2b) × (a - 2b)

Second expression = (4a2 + 4ab - 24b2)

                          = 4(a2 + ab - 6b2), by taking common 4

                      = 4(a2 + 3ab - 2ab - 6b2), by splitting the middle term ab = 3ab - 2ab

                         = 4[a(a + 3b) - 2b(a + 3b)]

                         = 4(a + 3b) (a - 2b)

                         = 2 × 2 × (a + 3b) × (a - 2b)

Third expression = (2a2 - 12ab + 16b2)

                      = 2(a2 - 6ab + 8b2), , by taking common 2

              = 2(a2 - 4ab - 2ab + 8b2), by splitting the middle term - 6ab = - 4ab - 2ab

                      = 2[a(a - 4b) - 2b(a - 4b)]

                      = 2(a - 4b) (a - 2b)

                      = 2 × (a - 4b) × (a - 2b)

From the above three expressions ‘2’ and ‘(a - 2b)’ are the common factors of the expressions.

Therefore, the required H.C.F. is 2 × (a - 2b) = 2(a - 2b)






8th Grade Math Practice

From H.C.F. of Polynomials by Factorization to HOME PAGE


New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.



Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.